Results of chemotherapy for pulmonary metastases of carcinoma of the cervix in patients after primary surgical and radiotherapeutic management. Issue 5 (1st September 2007) - Panek, G.; Gawrychowski, K.; Sobiczewski, P.; Derlatka, P.; Danska-Bidzinska, A.; Gmyrek, L.; Bidzinski, M.
Abstract : The purpose of this study was to evaluate the results of chemotherapy of pulmonary metastases from invasive carcinoma of the cervix, which were detected after a disease-free period after initial treatment with surgery or radiotherapy. Fifty patients with radiologically proven pulmonary metastases were treated with chemotherapy. All patients received a platinum-5-fluorouracil (PF) program: cisplatin 75 mg/m 2 and 5-fluorouracil 800 mg/m 2 every 4 weeks. The overall 1- and 3-year survival after PF chemotherapy was 62% and 17.6%, respectively. The progression-free survival at 1 and 3 years was 36.7% and 14.3%, respectively. There were 6 (12%) complete responses and 17 (34%) partial responses. Hematologic tolerance was acceptable. Third degree and fourth degree leukopenia was diagnosed in four (8%) and six (12%) patients, respectively. Three individuals had third degree thrombocytopenia. In the multivariate analysis, the following prognostic factors were associated with poor survival: time to recurrence after primary treatment ( P = 0.002), number of lung metastases ( P = 0.016), and progression during chemotherapy ( P = 0.001). We conclude that PF regimen is a safe and reasonably effective chemotherapy in the management of patients with pulmonary metastases after primary treatment for invasive carcinoma of the cervix who do not qualify for surgical metastasectomy.